Involvement of programmed death-ligand 2 (PD-L2) in the development of experimental allergic conjunctivitis in mice. Issue 8 (13th April 2006) - Fukushima, A; Yamaguchi, T; Azuma, M; Yagita, H; Ueno, H
Abstract : Background/aim: Involvement of programmed death-1 (PD-1) and its ligands has been demonstrated in experimental allergic airway disease. Here, the authors aimed to examine whether PD-1 and its ligands are involved in the development of experimental allergic conjunctivitis (EC) in mice. Methods: EC was induced in Balb/c mice by active immunisation with short ragweed pollen (RW) in alum. 10 days later (day 10), the mice were challenged with eye drops containing RW. 24 hours after the challenge, conjunctivas, spleens, and sera were harvested for histological analysis, cytokine assays, and measurement of RW specific Ig levels. The actively immunised mice were treated with anti-PD-1, anti-PD-L1, anti-PD-L2 antibodies (Abs), or normal rat immunoglobulin G (nrIgG) during either the induction (day 0, 2, 4, 6, and 8) or the effector (2 hours before RW challenge on day 10) phase. Results: Ab treatment during the induction phase did not affect eosinophil infiltration although immune responses were modulated. In contrast, treatment with anti-PD-L2 Ab, but not anti-PD-1 or anti-PD-L1 Ab, during the effector phase significantly increased eosinophil infiltration into the conjunctiva without affecting systemic immune responses. Conclusions: Similar to allergic airway inflammation, PD-L2 is involved in the development of EC during the effector phase but not the induction phase.